An Analysis of the First Language Acquisition: A Two Years Girl - Endah Ratnaningsih (Ahmad Dahlan Journal of English Studies, 2017)
As a natural process, human innateness understood as the ability in acquiring first language since birth. First language acquisition is related to this field of study. This study will focus on language acquisition of a two years girl who become the object of observation. However, the understanding of language acquisition and learning, then what factors are associated with language acquisition are regarded to be necessary to explain. Furthermore, on the discussion part, the analysis of the language acquisition on the object observed, both in terms of phonology, lexical, pragmatic, and the factors that influence the process of first language acquisition for the object observed are disscussed.